2019
DOI: 10.1016/j.rpor.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing MRI sequences and images for MRI-based stereotactic radiosurgery treatment planning

Abstract: Aim: Development of MRI sequences and processing methods for the production of images appropriate for direct use in stereotactic radiosurgery (SRS) treatment planning.Background: MRI is useful in SRS treatment planning, especially for patients with brain lesions or anatomical targets that are poorly distinguished by CT, but its use requires further refinement. This methodology seeks to optimize MRI sequences to generate distortion-free and clinically relevant MR images for MRI-only SRS treatment planning. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…They reported that distortions depend on the type of MR sequence and on the proximity of the base of the stereotactic headframe to the region of interest. Distortions range from <0.5 mm near the center of the stereotactic space to about 2.0 mm near the base of the headframe 39,54,56–59 . For 3 Tesla MR scanners, larger distortions have been reported, ranging from 1.0 to 4.0 mm 56,60,61 .…”
Section: Treatment Process Quality Assurancementioning
confidence: 99%
See 1 more Smart Citation
“…They reported that distortions depend on the type of MR sequence and on the proximity of the base of the stereotactic headframe to the region of interest. Distortions range from <0.5 mm near the center of the stereotactic space to about 2.0 mm near the base of the headframe 39,54,56–59 . For 3 Tesla MR scanners, larger distortions have been reported, ranging from 1.0 to 4.0 mm 56,60,61 .…”
Section: Treatment Process Quality Assurancementioning
confidence: 99%
“…Distortions range from <0.5 mm near the center of the stereotactic space to about 2.0 mm near the base of the headframe. 39,54,[56][57][58][59] For 3 Tesla MR scanners, larger distortions have been reported, ranging from 1.0 to 4.0 mm. 56,60,61 For cases where significant distortions might be expected in the MR scan (e.g., due to surgical clips), a stereotactic CT scan should be obtained for treatment planning.…”
Section: B1 Imagingmentioning
confidence: 99%
“…A high SNR is beneficial in many ways for SRS treatment. For example, the resulting high-quality MR images allow easy localization of lesions [21, 22]. Alternatively, we can increase the spatial resolution of the image if we maintain the SNR at the level of a single-channel coil [23]; that is, high-resolution brain imaging is possible with multichannel coils at the expense of SNR.…”
Section: Discussionmentioning
confidence: 99%
“…As it is performed as provided SMGAN-3D can given high level image quality from the existing denoising networks. Optimizing MRI sequence and images for MRI-based stereotactic radiosurgery treatment planning [4] This paper title present the work done on MRI sequence and processing method on human brain scanning by the direct use of stereotactic radiosurgery(SRS) as it define the noisy or harmful impact cause on body during CT(as ionizing radiation). In this, it revolves around the comparison between CT and SRS technique used by MRI.…”
Section: Literature Surveymentioning
confidence: 99%